الذكاء الاصطناعي في تعليم الفيزياء الحديثة للمرحلة الثانوية فرص للتطوير وتحديات للتنفيذ - علي, ولاء عبدالرزاق (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study focuses on developing and implementation artificial intelligence – based physics teaching strategies for secondary school female students, many educational institutions have adopted artificial intelligence tools thanks to rapid developments in this field. Teachers can save time and effort in improving student learning outcomes by using artificial intelligence – based solutions in classroom, making the educational process more interactive & easier. The study aimed to determin the extent to which physics teachers in Diyala Governorate, Baqubah District, use artificial intelligence application's in teaching physics at the secondary level, as villas the role of academic qualificatious in teachers willingness to use artificial intelligenic in teaching, and the obstacles they face. The questionnaire was used, and the study reached aset of results, the most important of which are: physics teachers in teaching physics at the secondary level in employ artificial intelligence applications Baqubah city at a moderate level. The study also found statistically significant difference in the academic qualification variable in favor of those with higher degress. it also showed that most of the obstacles to employing artificial intelligence applicatious in teaching physics at the secondary level are common in Baqubah schools. These include alack of experience in inversting in artificial intelligence in teaching, alack of training program's and courses in this field, and alack of motivation and financial support for teachers to encourage them to use these applications in teaching physics.